India's Asia-Pacific Engagement : Impulses and Imperatives - Ram,Amar Nath, (Brill | Manohar Publishers & Distributors, 2015)
India's Asia-Pacifc engagement, now in its third decade, has become an integral and irreversible plank of our foreign policy. This volume seeks to provide a new and unique perspective to the discourse on the evolving Look East Policy, updating, assessing, critically evaluating and analyzing developments beyond its first two decades and looking into the impulses and imperatives of India's growing and deepening engagement with the larger and rapidly changing geo-political space of the Asia-Pacifc region, which some now have begun to describe as the Indo-Pacifc. The essays in this compilation, written by former practitioners and some eminent experts, cover various aspects of our evolving engagement, going beyond the ASEAN geo-political space and the hitherto traditional areas of focus, importantly now covering strategic, security, political, economic, cultural and the diaspora aspects of our enlarged engagement, also suggesting a road map and specifc next steps for enduring partnership in the coming decade. The personal insights, analysis and candid perspectives offered by the contributors makes this volume unique and one of its kind.